Tanggung Jawab Perusahaan Transnasional terhadap Pelanggaran HAM dalam Perspektif Hukum Internasional - Sefriani Sefriani (Unisia, 2007)
Recognition of Transnational Enterprises (TNEs) as subjects of international law is unclear, and therefore, their responsibilities are also ambiguous. As a consequence, various violations of human rights committed by the TNEs in some developing and least-developed countries, both in the era of World War II and in the era of globalization were left enforceable. Recently, there are some international law instruments imposing obligation directly on the TNEs. Despite being soft laws and having some weaknesses, these instruments can be considered as the international customary laws, having legal binding upon all nations. This article argues that it is urgent to establish a new system of TNEs responsibility, and to learn and compare between individual and state responsibility systems in human rights violations. This is because TNEs are entities that are more than individual persons but less than the State. Keywords: Human rights violation, responsibility, TNEs.